Scrutinising the role of the Police and Crime Panel in the new era of police governance in England and Wales. Issue 1 (7th January 2014) - Lister, Stuart
Abstract : Purpose: – The purpose of this paper is to explore the role of Police and Crime Panels (PCPs) within the new constitutional arrangements for governing police forces in England and Wales. Design/methodology/approach: – Desktop research of the web pages of PCPs, combined with documentary analysis of reports of panel meetings and a literature review of relevant academic materials. Findings: – During the first year of their operation the role of the PCP in the new constitutional arrangements for governing police forces in England and Wales has been widely criticised. This paper explores reasons that may impinge on the effectiveness of these local bodies to scrutinise how Police and Crime Commissioners discharge their statutory functions. In particular, it draws attention to the limited powers of the panel, the contradictions of the "critical/friend" model of scrutiny, the extent of political alignment between "the scrutinisers" and "the scrutinee", and the ability of the latter to constrain the scrutiny function of the former. Originality/value: – This paper is the first to explore the scrutiny role of PCPs in the context of the research evidence regarding the development and use of scrutiny within the local government context.